Antimicrobial activity of Balsam Apple (Mormodica balsamina L.) - Abubakar Bello; Fatima Muhammad; Sulaiman S. Kankara; Bashir Abdulkadir; Buhari Y. Shinkafi (UMYU Journal of Microbiology Research)
Momordica balsamina L. commonly known as African pumpkin or Balsam apple (Cucurbitaceae) is used as vegetable in many African countries and traditionally in the treatment of skin diseases. In this study, phytochemical prospective and antimicrobial activities of its leaf extracts were evaluated with the view to validating its medicinal potentials. Acetone, ethanol and water were used as the extracting solvents. Presence of various secondary metabolites as tannins, flavonoids, proanthocyanidins, alkaloids and saponins were observed. Acetone extract indicated a significant inhibition in all the bacterial isolate (Escherichia coli, Staphylococcus aureus, and Salmonella typhi) tested at 100 mg/ml (P<0.05) followed by ethanol extract which inhibited the growth of E. coli and S. aureus. The water extract showed a significant (P<0.05) inhibition on the growth of E. coli and Sa. typhi. The result of antifungal assay showed that acetone extract suppressed the growth of Aspergillus niger and Rhizopus sp at 100 mg/ml. The results obtained provided a scientific support for the claimed ethnomedicinal uses of the leaves of M. balsamina and suggested its potential as a source of a lead compound in the treatment of microbial infections. Key words: Acetone, Bacteria, ethnobotany, Fungi, Methanol, water